2022
DOI: 10.1111/den.14350
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic resection via antral submucosal tunneling for en bloc removal of tumors in the duodenal bulb

Abstract: To overcome difficulties in the removal of duodenal bulb lesions, especially those in anatomically challenging locations, we developed the endoscopic resection via antral submucosal tunneling (ERAST) technique. In this study, we evaluated the feasibility and safety of ERAST for the removal of superficial and subepithelial lesions in the duodenal bulb. This was a single‐center retrospective study of 10 patients with lesions in the bulb. Submucosal tunneling from the gastric antrum to the duodenum was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Despite its efficacy, the potential for submucosal tunneling injuries should not be overlooked. Luo et al ( 9 ) reported a 100% success rate in en bloc resection for lesions in the duodenal bulb via STER, with no significant bleeding and only a minor micro-perforation, approximately 3 mm in width. However, these findings, while promising, underscore the necessity for larger clinical studies to validate the safety and effectiveness of STER in broader patient populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its efficacy, the potential for submucosal tunneling injuries should not be overlooked. Luo et al ( 9 ) reported a 100% success rate in en bloc resection for lesions in the duodenal bulb via STER, with no significant bleeding and only a minor micro-perforation, approximately 3 mm in width. However, these findings, while promising, underscore the necessity for larger clinical studies to validate the safety and effectiveness of STER in broader patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…Additional treatment modalities include immunotherapy, peptide receptor radioligand therapy, somatostatin analog therapy, symptomatic management, and endoscopic resection. In China, the methods of endoscopic resection, including endoscopic submucosal excavation (ESE) ( 7 ), endoscopic submucosal dissection (ESD) ( 8 ), and submucosal tunneling endoscopic resection (STER) ( 9 ) are increasingly favored for treating these smaller and less invasive NETs, due to their reduced risk of complications. Moreover, endoscopic resection serves as an intermediate strategy that bridges the gap between a “watch-and-wait” approach and surgery according to the horizontal and vertical margins.…”
Section: Introductionmentioning
confidence: 99%
“…Additional treatment modalities include immunotherapy, peptide receptor radioligand therapy, somatostatin analog therapy, symptomatic management, and endoscopic resection. In China, the methods of endoscopic resection, including endoscopic submucosal excavation (ESE) (7), endoscopic submucosal dissection (ESD) (8), and submucosal tunneling endoscopic resection (STER) (9) are increasingly favored for treating these smaller and less invasive NETs, due to their reduced risk of complications. Moreover, endoscopic resection serves as an intermediate strategy that bridges the gap between a "watch-and-wait" approach and surgery according to the horizontal and vertical margins.…”
Section: Introductionmentioning
confidence: 99%